Elevated Axonal Protein Markers Following Repetitive Blast Exposure in Military Personnel - Vorn, Rany; Naunheim, Rosanne; Lai, Chen; Wagner, Chelsea; Gill, Jessica M. (Frontiers in Neuroscience, 2022)
Blast exposures that occur during training are common in military personnel; however, the biomarkers that relate to these subtle injuries is not well understood. Therefore, the purpose of this study is to identify the acute biomarkers related to blast injury in a cohort of military personnel exposure to blast-related training. Thirty-four military personnel who participated in the training program were included in this study. Blood samples were collected before and after repetitive blast-related training on days 2 (n = 19) and days 7 (n =15). Serum concentration (pg/mL) of tau, glial fibrillary acidic protein (GFAP), neurofilament light chain (NfL), and phosphorylated tau181 (p-tau181) were measured using an ultrasensitive immunoassay platform. We observed that serum p-tau181 concentrations were elevated after exposed to repetitive blast on days 2 (z = -2.983, p = 0.003) and days 7 (z = -2.158, p = 0.031). Serum tau (z = -2.272, p = 0.023) and NfL (z = -2.158, p = 0.031) levels were significantly elevated after exposure to repetitive blasts on days 7. Our findings indicate that blast exposure affects serum biomarkers indicating axonal injury.